The Use of Cross-Domain Language by Expert Software Developers. - Weitzenfeld, Julian; Riedl, Tom; Chubb, Charles; Freeman, Jared (Metaphor & Symbolic Activity, 1992)
The language and thought of expert software developers is permeated by characteristic terminology that crosses domains of reference, but there are interesting questions about whether these usages are metaphoric. The observations we report here were made during a study of the expertise of software engineers, conducted as part of a project to develop training in how to debug large software systems (Riedl, Weitzenfeld, Freeman, Klein, & Musa, 1991; Weitzenfeld, Riedl, Freeman, Klein, & Musa, 1991). Certain seeming metaphors were so salient in our informants' speech that they featured prominently in the resulting course.